Performance of Adsorbent from Calcium Carbide Residue to Reduce Exhaust Emissions of Two-wheeler - Hendry Sakke Tira; Made Wirawan; Samsul Rahman; Ekarong Sukjit; Sudirman Sudirman (Automotive Experiences, 2023)
The performance of calcium carbide residue in reducing two-wheel exhaust emissions has been studied. To perform this experiment, the carbide residue was first converted into adsorbent and then mounted in the exhaust gas line. Two-wheeler used are vehicles commonly used among Indonesian motorcyclists. The test was carried out by varying the adsorbent dimensions and engine transmission. Engine emission tests and adsorbent performance investigations were performed both before and after the exhaust emissions made contact with the adsorbent. The results showed that upon direct contact with the carbide adsorbent, the emission of two-wheeled engines decreased. Carbon-based emissions were reduced significantly in the early stages of the experiment. Moreover, emissions reduction benefits are seen in all adsorbent and transmission engine configurations. The greater the adsorbent's surface area, the better the emission reduction. A significant emissions reduction is also achieved when the first engine transmission condition is applied compared to the neutral transmission. However, the adsorption efficacy declined over time in all research variations. The presence of channels and pores in the adsorbent, and the high temperature attained by the adsorbent, keep improving the adsorbent's adsorption capabilities. However, as saturation increases, the adsorbent's adsorption, and oxidation capability decline.